Treasure Island - "Louis, Robert Stevenson" (OUP Karachi)
If you like action-packed adventure, then Treasure Island is the story for you! Not only does this edition include the complete, unabridged text, it is also full of extra material to help you get the most from the story and gives lots of recommendations for other adventures you might enjoy.
Keywords: English- Textbook